PENGARUH HIPNOTERAPI TERHADAP PENURUNAN TINGKAT KECEMASAN (ANXIETY) AKIBAT PANDEMI COVID-19 DI KOTA MAKASSAR - Andi Mahdi Sahdani (Jurnal EMPATI, 2023)
Anxiety is one of the psychological impacts felt by individuals in the face of the Covid-19 pandemic. Anxiety due to the Covid-19 pandemic arises because of the stimulus related to the Covid-19 pandemic that is received by individuals. Stimulus related to the Covid-19 pandemic that is not processed properly in the cognitive realm causes anxiety and has the potential to reduce individual immunity. Individuals who experience decreased body immunity are susceptible to contracting various diseases, including Covid-19. This study aims to determine the effect of hypnotherapy intervention on reducing anxiety levels due to the Covid-19 pandemic. This research design uses a quasi-experimental research design with one group pretest-posttest research design. Participants in the study consisted of 8 women aged 21-30 years who experienced anxiety due to the Covid-19 pandemic. The measuring instrument used in this study is the Coronavirus Anxiety Scale (CAS) which has been adapted into Indonesian. The data analysis technique used the Wilcoxon test. The results showed that hypnotherapy had an effect on reducing anxiety levels due to the Covid-19 pandemic ( pretest=7.375,  posttest=0.875, ρ=0.007). The implication of this research is that hypnotherapy can be used as an alternative method to reduce anxiety levels due to the Covid-19 pandemic.